2020
DOI: 10.1111/dth.13686
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive and immunomodulator therapy for rare or uncommon skin disorders in pandemic days

Abstract: Immunosuppressive and immunomodulatory therapies are important in dermatology, but indications are influenced by SARS-CoV-2. We will focus on skin disorders such as autoimmune connective tissue disorders, neutrophilic dermatoses, and vasculitis. Immunomodulators such as colchicine and antimalarials can easily be preferred taking their beneficial effects on COVID-19 into consideration and also given their wide spectrum of action. Among the conventional therapies, methotrexate, azathioprine, and mycophenolate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 115 publications
(127 reference statements)
0
25
0
Order By: Relevance
“…During this period, it is recommended to reduce its dose to below 0.5 mg/kg/ day. 12 We reduced the azathioprine doses in seven of our patients in line with the recommendations.…”
Section: T a B L E 1 The Clinical Characteristics Of The Patients Witmentioning
confidence: 87%
See 1 more Smart Citation
“…During this period, it is recommended to reduce its dose to below 0.5 mg/kg/ day. 12 We reduced the azathioprine doses in seven of our patients in line with the recommendations.…”
Section: T a B L E 1 The Clinical Characteristics Of The Patients Witmentioning
confidence: 87%
“…7 Discussions continue about the use of these treatments during the COVID-19 pandemic period. 4,12 It is known that the risk of upper respiratory infections increases with the use of these agents. This condition can be a risk for the pandemic period.…”
Section: T a B L E 1 The Clinical Characteristics Of The Patients Witmentioning
confidence: 99%
“…However, the main adverse effects of cyclosporine, such as hypertension and renal dysfunction, may pose more severe risks for patients contracted COVID‐19. It should be noted that patients with hypertension are more prone to develop severe COVID‐19 infection 23 . Unexpectedly, Wilde reported that cyclosporine strongly inhibits in vitro replication of MERS‐coronavirus, while its in vivo effects remain unknown 24 …”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that patients with hypertension are more prone to develop severe COVID-19 infection. 23 Unexpectedly, Wilde reported that cyclosporine strongly inhibits in vitro replication of MERS-coronavirus, while its in vivo effects remain unknown. 24 Despite the impact of these immunosuppressive agents on the course of COVID-19 is clearly unknown, several dermatology societies have recommended to withdrawn or suspend immunosuppressive treatments in the case of COVID-19 diagnosis until the patient recovers from the infection.…”
Section: Methotrexate and Cyclosporinementioning
confidence: 99%
“…If not responsive to CS, switch to IVIG, anakinra, cyclosporine, or adalimumab. 70 Scleroderma Avoid systemic CS, MTX. Discontinue biologics if possible.…”
Section: Lupus Erythematosusmentioning
confidence: 99%